PENGARUH BRAND AWARENESS DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ERIGO PADA MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Zulfanah, Putri Maria; Mulyati, Awin; Maduwinarti, Ayun (Research Journal of Social Science and Economics, 2025)
In today’s modern era, the need for the world of fashion is getting bigger. Various types of brands have sprung up in Indonesia. One of them is the Ergo brand. Erigo is one of the local clothing brand names that elevates and promotes products that are comfortable to wear, affordable prices, varied designs and motifs, and a large selection of colors that make Erigo much in demand by buyers. In this study, it explains the effect of Brand Awareness and Digital Marketing on Purchasing Decisions of Erigo products for students at the University of 17 Agustus 1945 Surabaya. This study aims to determine how significant the influence of Brand Awareness and Digital Marketing on the Purchase Decision of Erigo products for students at the University of 17 August 1945 Surabaya. This study used a quantitative method with a questionnaire research instrument or a questionnaire made by the researcher himself. The population in this study were students at the University of 17 Agustus 1945 Surabaya who had bought Erigo products. The data analysis technique used in this research is instrument test, classical assumption test, multiple linear regression test, determination test, and hypothesis test. The results of this study indicate that Brand Awareness and Digital Marketing have a positive and significant influence, either partially or simultaneously on the Purchase Decision of Erigo products for students at the University of 17 August 1945 Surabaya.